Rehabilitation of a partial glossectomy patient: Palatal augmentation prosthesis - Payal Rajender Kumar; Anurag Hasti; H G Jagadeesh; Bishwachandra Thoudam (Wolters Kluwer Medknow Publications, 2019)
Tongue-palate contact is necessary for the production of normal speech, and the proper location of the tongue on the palate during certain sounds is important. Partial glossectomy leads to difficulty in tongue-palate articulation during speech, and it becomes difficult for a patient to reach the palate with the tongue to form certain sounds. In-depth knowledge of the production of different sounds can be used as a diagnostic aid in determining the thickness of the palatal augmentation prosthesis fabricated to rehabilitate such patients. A functional wax technique is used to make a functional impression of tongue-palate contact during the speech.